The Influence of Social Media Advertisements on Instagram, Tiktok, and Facebook on Consumer Purchase Interest in Fashion Products on The Shopee Application - Astiana Nehem; Cakti Indra Gunawan; Anung Prasetyo Nugroho; Elly Lestari (International Journal of Management and Business, 2026)
Digital technology development in Indonesia has transformed communication and marketing practices, with social media emerging as a primary promotional tool due to its wide and rapid reach. In the context of intense competition in the fashion industry, companies are increasingly required to leverage platforms such as Instagram, TikTok, and Facebook to stimulate consumer purchase interest. This study aims to analyze the effect of social media advertising on Instagram, TikTok, and Facebook on purchase intention of fashion products on the Shopee application among students of Tribhuwana Tunggadewi University class of 2024. This research uses a quantitative method with data collection techniques through questionnaires distributed to 91 respondents using purposive sampling. Data analysis was conducted using multiple linear regression with SPSS. The results show that partially, Instagram and Facebook advertisements have a significant effect on purchase intention, while TikTok advertisements do not have a significant effect. Simultaneously, all social media advertising variables influence purchase intention. The coefficient of determination (R²) is 0.321, indicating that 32.1% of purchase intention is explained by Instagram, TikTok, and Facebook advertising, while the remaining is influenced by other factors outside this study. Social media advertising demonstrates differing impacts on purchase intention for fashion products on Shopee. Nevertheless, the combined influence of Instagram, TikTok, and Facebook remains significant, underscoring the importance of multi-platform strategies in strengthening consumer perceptions and driving purchase intention.